Effectiveness of the Distribution of KUR (People's Business Credit) for the Development of Micro, Small and Medium Enterprises in Pangkalpinang City - Julia, Julia; Khairiyansyah (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
People's Business Credit (KUR) is a credit guarantee program, where this program is channeled to MSMEs who need additional loan funds for their businesses so that they can increase business productivity. After the program runs, the guarantee institution ensures that the program has been running productively or effectively so that the target for the distribution of the KUR program is achieved. The purpose of this study was to analyze the effectiveness of the distribution of People's Business Credit (KUR) and its effect on improving the performance of micro and small enterprises. The type of research used in this research is descriptive research. Descriptive research pays attention to the actual problem as it was at the time the research took place. Through descriptive research, researchers try to describe events and events that are the center of attention without special treatment for these events. The last stage in data analysis is drawing conclusions and verification. The results of this study indicate that KUR in the city of Pangkalpinang can be said to be effective, because it has met the requirements set by the government.